2020
DOI: 10.1111/jvim.15711
|View full text |Cite
|
Sign up to set email alerts
|

Serum procalcitonin concentrations in dogs with induced endotoxemia

Abstract: Background Procalcitonin (PCT) is an important biomarker for sepsis in human medicine, but there is little information regarding PCT as a biomarker for sepsis in dogs. There are no controlled studies evaluating serial concentrations of PCT in dogs. Hypothesis/Objective That PCT would be rapidly detectable in serum after injection of LPS and would remain increased for at least 24 hours. Objective was to evaluate serial serum PCT concentrations in dogs after a single IV injection of LPS compared to placebo. Anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 29 publications
5
23
0
1
Order By: Relevance
“…Previously recognized temporal responses of APPs and other biomarkers to an inflammatory stimulus were recapitulated here. 64 , 65 , 66 , 67 , 68 Haptoglobin is a minor APP in dogs with delayed onset and resolution relative to CRP and SAA, 65 , 69 and its delayed normalization here was consistent with a study of dogs with pyometra. 30 …”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Previously recognized temporal responses of APPs and other biomarkers to an inflammatory stimulus were recapitulated here. 64 , 65 , 66 , 67 , 68 Haptoglobin is a minor APP in dogs with delayed onset and resolution relative to CRP and SAA, 65 , 69 and its delayed normalization here was consistent with a study of dogs with pyometra. 30 …”
Section: Discussionsupporting
confidence: 89%
“…For CRP, the median (IQR) times to 20% peak and to RI were 7 (6-9) and other biomarkers to an inflammatory stimulus were recapitulated here. [64][65][66][67][68] Haptoglobin is a minor APP in dogs with delayed onset and resolution relative to CRP and SAA, 65,69 and its delayed normalization here was consistent with a study of dogs with pyometra. 30 We also aimed to compare time to biomarker normalization with AMD duration and the time to biomarker normalization across diseases.…”
Section: Biomarkers Vs Antimicrobial Drug Prescribingsupporting
confidence: 89%
See 1 more Smart Citation
“…A recent canine study investigated the association between PCT and induced endotoxemia in 16 dogs. The results showed a significant increase in PCT serum concentrations after injection of lipopolysaccharide, suggesting that PCT is influenced by bacteria‐related inflammation and might be a marker for such disease processes 34 . The present study showed that dogs with acute diarrhea had increased serum PCT concentrations, even if they were not septic.…”
Section: Discussionsupporting
confidence: 59%
“…Goggs et al [ 12 ] confirmed that the Biovendor canine PCT ELISA assay was able to detect canine PCT and can be used to determine plasma PCT concentrations in dogs. Furthermore, Easley et al [ 13 ] reported the evaluation of PCT concentrations in dogs as a prognostic factor by using the same recombinant ELISA kit. Yilmaz et al [ 14 ] reported the use of a commercial human ELISA kit for the detection of canine PCT but no validation data are reported.…”
Section: Introductionmentioning
confidence: 99%